The calcium wave model of the perception-action cycle: Evidence from semantic relevance in memory experiments - Pereira Jr., Alfredo [UNESP]; dos Santos, Rafael Peres [UNESP]; Barros, Rafael Fernandes [UNESP] (Frontiers, 2013)
We present a general model of brain function (the calcium wave model), distinguishing three processing modes in the perception-action cycle. The model provides an interpretation of the data from experiments on semantic memory conducted by the authors. © 2013 Pereira Jr, Santos and Barros.
Keywords: Action; Consciousness; Learning; Memory; Perception; Relevance; Repetition